1996
DOI: 10.1002/(sici)1098-2752(1996)17:12<714::aid-micr10>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental prevention of free flap thrombosis. II: Normovolemic hemodilution for thrombosis prevention

Abstract: A microvascular free flap failure model consisting of raising an epigastric groin flap on the femoral pedicle, while cutting the femoral artery, twisting it around the femoral vein and resuturing it, has been previously described. As it was being evaluated, normovolemic hemodilution as a means to prevent thrombosis was simultaneously assessed using an additional experimental group. Twenty percent of the blood mass of each rat was taken and replaced with a hydroxyethyl starch solution immediately before surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…On the other hand, it could improve oxygenation because of increased microcirculatory blood flow. In experimental studies, normovolaemic haemodilution reduces risk of thrombosis [13] and increases flap oxygenation [14]. In clinical studies, the debate of deliberate fluid therapy versus restrictive fluid therapy is still ongoing [15, 16], although a recent review favours restrictive fluid therapy [3].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it could improve oxygenation because of increased microcirculatory blood flow. In experimental studies, normovolaemic haemodilution reduces risk of thrombosis [13] and increases flap oxygenation [14]. In clinical studies, the debate of deliberate fluid therapy versus restrictive fluid therapy is still ongoing [15, 16], although a recent review favours restrictive fluid therapy [3].…”
Section: Discussionmentioning
confidence: 99%
“…21 Atchabahian and Masquelet replaced 20% of the experimental group's blood with a hydroxyethyl starch solution. 26 In both studies, the experimental groups suffered a lower incidence of flap failure. Similarly, Earle et al found that flap survival length was increased in dogs that were preoperatively rendered anemic by replacement of some blood with lactated Ringer's solution.…”
Section: Discussionmentioning
confidence: 97%
“…Animal studies using HES (12), albumin (13) confirm the reduction in venous thrombosis by using this technique. SIGURDSSON (2) and CONRAD et al (14), studying pharmacologic optimization in microsurgery, recommended haemodilution (in particular with dextran 0,4 ml/kg/hour) as ideal thromboprophylaxis.…”
Section: Normovolaemic Haemodilutionmentioning
confidence: 99%